-56=-4(3+x)

Simple and best practice solution for -56=-4(3+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -56=-4(3+x) equation:



-56=-4(3+x)
We move all terms to the left:
-56-(-4(3+x))=0
We add all the numbers together, and all the variables
-(-4(x+3))-56=0
We calculate terms in parentheses: -(-4(x+3)), so:
-4(x+3)
We multiply parentheses
-4x-12
Back to the equation:
-(-4x-12)
We get rid of parentheses
4x+12-56=0
We add all the numbers together, and all the variables
4x-44=0
We move all terms containing x to the left, all other terms to the right
4x=44
x=44/4
x=11

See similar equations:

| 43p+725=p | | 7x-132=84+15x | | –2−7m=–6m | | -(f+14)=3 | | 5(x-4+x=6-2x)+8 | | 8+16x-9=x+8 | | x2-11x-10=0 | | 5x+1=62=18x+11 | | 6x+7=9x+4 | | 2x+30=2x-8 | | -2(p+2)=-10 | | -1+7x=125 | | 3/4b-14=15 | | 0.08(y-7)+0.20=0.18y-1.2 | | 2(5x+3)=6-3x | | -14q-1-5q=-5-19q | | 6d+10=4d-20 | | -12t-7=-12t=10 | | X/7=(3x+2)/20 | | 3x+7(x-4)=2 | | -8j=-16 | | 81.6=8(m+3.6 | | 7x-7x10=25 | | 10-y=-1 | | 5x+4+7x-2+8x-5=180 | | –6x+18=–60 | | 5-1(x+10)=4x+10 | | 7x-0=25 | | x=(x-3) | | 6n-20=4-10n | | -13t-7=-7+7t-10t | | 2/6x+9=21 |

Equations solver categories